REAGENT FOR ANALYSIS OF WHITE CORPUSCLES - SAKATA TAKASHI (1995)
PURPOSE:To classify white corpuscles into four subgroups by using a low cost and simple structure apparatus without using a toxic chemical by a method wherein an ionic surface-active agent which is repressed by a specific formula, an organic compound which has an anion group, a nonionic surface active agent and a buffer agent for pH adjustment are contained in the reagent. CONSTITUTION:A reagent is composed of (a) an ionic surface active agent which can dissolves red corpuscles, whose amount is sufficient to damage a part of the cell membrane of white corpuscles and which is expressed by the formula, of (b) an organic compound which is bonded to a cation charged component inside the white corpuscles and which has an anion group sufficient to give a morphological difference between the white corpuscles, of (c) a nonionic surface active agent and of (d) a buffer agent for pH adjustment. In the formula, R1 represents an alkyl group and an alkenyl group of C6 to 18, R2 and R3 represent an alkyl group and an alkenyl group of C1 to 4, R4 represents an alkyl group and an alkenyl group or a benzyl group of C1 to 4, and X represents halogen atoms. It is sufficient that the ionic surface-active agent has a hemolytic force capable of opening a slender hole, in the white corpuscles, through which the organic compound can be passed.